2015
DOI: 10.1111/1365-2435.12471
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient limitation of woody debris decomposition in a tropical forest: contrasting effects of N and P addition

Abstract: Summary1. Tropical forests represent a major terrestrial store of carbon (C), a large proportion of which is contained in the soil and decaying organic matter. Woody debris plays a key role in forest C dynamics because it contains a sizeable proportion of total forest C. Understanding the factors controlling the decomposition of organic matter in general, and woody debris in particular, is hence critical to assessing changes in tropical C storage.2. We conducted a factorial fertilization experiment in a tropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 54 publications
3
25
0
Order By: Relevance
“…The soil is classified as a latosol developed from granite (Wang et al, ). Annual wet N deposition in the region was c. 40 kg N/ha in 2011 and 2012 (Chen et al, ; Mo et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The soil is classified as a latosol developed from granite (Wang et al, ). Annual wet N deposition in the region was c. 40 kg N/ha in 2011 and 2012 (Chen et al, ; Mo et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Nitrogen fertilization (150 kg N/ha/yr) in N‐rich mature tropical forests in southern China showed no effect on bulk soil C storage, although more labile fractions of SOM declined with N fertilization after 4.5 years [ Liu et al ., ], suggesting stimulation of microbial decomposition rates for some portion of SOM. In contrast, another study on highly weathered soils in southern China observed no effect of N fertilization (150 kg N/ha/yr) on decomposition of woody SOM after 3 years [ Chen et al ., ]. These two Chinese studies suggest that decomposition rates of labile versus woody fractions of SOM may respond differently to N additions, with net changes in soil C storage apparent only if the relative magnitudes of the effects are not in balance.…”
Section: Review Of Global Change Effects On Tropical Ecosystemsmentioning
confidence: 98%
“…, Kaspari and Yanoviak , Chen et al. ). Unlike nutrients, C is overabundant in essentially all soils of the different tropical forest ecosystems discussed here, with C:nutrient ratios largely exceeding those of soil microbial biomass (Cleveland and Liptzin ).…”
Section: The Role Of Carbon Availabilitymentioning
confidence: 99%